An Expected Average Run Length (EARL) Performance Comparison of the SSGR and EWMA Control Charts - You, H. W.; Chong, Z.L.; Teoh, W. L.; Khoo, M.B.C.; Yeong, W.C. (International Journal of Integrated Engineering, 2023)
The acceleration use of control charts in industrial processes has led to the effectiveness in their evaluation by quality practitioners. This is crucial, as it influences their decisions on the choice of which control charts to employ. This study aims to explore and compare the performance of the side sensitive group runs (SSGR) and exponentially weighted moving average (EWMA) control charts. In general, the average run length (ARL) characteristics were used to evaluate the performance of these control charts. The ARL, which considers the exact shift size in the process, is restricted in the case when the practitioner cannot identify the process shift size (unknown shift size). In this situation, the expected average run length (EARL) is an alternative performance criterion. Upon comparison of the findings obtained, the EWMA chart has superior performance when (?min, ?max) = (0.1, 0.4). In contrast, the SSGR chart overtakes the EWMA chart when (?min, ?max) = (0.5, 0.8) and (?min, ?max) = (0.9, 1.2), except when the sample size n = 3 for (?min, ?max) = (0.5, 0.8). For this particular combination, the EWMA chart performs slightly better than the SSGR chart. The outcome of this study is expected to contribute to practitioners in identifying suitable control charts in process monitoring and implementation.